Indirect in vitro Regeneration in Four Varieties of Potato (Solanum tuberosum L.) from Internodal Segments and Leaf Explants (Plant Tissue Culture and Biotechnology, 2024)
Internodal segments and leaf explants from four varieties of potato (Solanum tuberosum L.) cultivated in Bangladesh, namely, Asterix, Diamant, Granola and Lady Rosseta were utilized for indirect in vitro regeneration of shoots through callus culture. The best responses regarding the reaeration of shoots were obtained when the explants were cultured on MS medium supplemented with 4.0 mg/l BAP and 1.0 mg/l IAA and 0.5 mg/l GA3. The highest frequency of multiple shoot regeneration was recorded from internodal segments rather than from the leaf explants. Hormone free MS medium was found to be the most effective for healthy root induction from the in vitro raised excised shoots. Following adequate root induction, the in vitro regenerated plantlets were successfully transplanted and established to soil for further growth and development of tubers. Plant Tissue Cult. & Biotech. 34(1): 83-92, 2024 (June)